3D printing of non-assembly mechanisms - Lai, David Yong Kuang (Nanyang Technological University, 2022)
With the advancement of addictive manufacturing and 3D printing in general, the printing of non-assembly mechanisms (NAMs) is made viable. It is highly desirable due to the lowering of parts count and minimal post-processing required to produce mobile mechanisms straight after fabrication. However, the nature of addictive manufacturing poses unique challenges in printing these NAMs compared to traditional production methods. The objective of this project is to collate and evaluate design considerations required for a successful print of a NAM, simple or complex. After evaluating the current research done on this topic, the simplest NAM, a 4-bar linkage, was printed and tested. This is followed by printing a more complex 8-bar linkage based on evaluation made from the printed 4-bar linkage. Both linkages were observed to be sufficiently mobile and the thought process behind 3D printing of NAMs was established for future prints, keeping in mind all the limitations and constrains surrounding 3D printing of NAMs. However, there are still areas of improvement in this design process, and future work should be undertaken to refine this process further.